Generic recircumscription in the Loxocarpinae (Gesneriaceae), as inferred by phylogenetic and morphological data. Issue 2 (3rd May 2016) - Puglisi, Carmen; Yao, Tze Leong; Milne, Richard; Möller, Michael; Middleton, David J.
Abstract: The Loxocarpinae, also known as the " Boea group", are the subtribe of Gesneriaceae which includes Boea and a number of segregated genera and close relatives. This group currently comprises over 200 species in 15 genera. Here we present the most up‐to‐date phylogeny, covering all the genera known to belong to the group, based on Bayesian inference and parsimony of the nuclear ITS and the plastid regions trnL‐trnF (intron and spacer) and ndhF‐trnL UAG (spacers). The results show discrepancies between the current generic delimitation in the subtribe and the clades delineated by the phylogeny. As a result Boea, Damrongia, Paraboea and Streptocarpus are recircumscribed in an attempt to establish a more natural classification and new combinations are made. The new genus Middletonia is described.